2020
DOI: 10.1016/j.wneu.2020.08.154
|View full text |Cite
|
Sign up to set email alerts
|

Common Carotid Artery Occlusion in a Young Patient: Can Large-Vessel Stroke Be the Initial Clinical Manifestation of Coronavirus Disease 2019?

Abstract: Background The occurrence of large-vessel occlusion in young patients with coronavirus disease 2019 (COVID-19) infection has been exceedingly rare. An extensive review of reported studies revealed a few reported cases. In the present report, we have described the clinical presentation, radiological findings, and outcome of large-vessel occlusion in a young patient with COVID-19 and reviewed the pertinent reported data on this condition. Case Description A 31-year-old wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
0
11
0
1
Order By: Relevance
“…This was the result of the inflammatory response and cytokine storm, which has also been considered as an important phenomenon for cardiac events in our review (Figure 2 ). Similarly, Alkhaibary et al [ 181 ] reported complete occlusion of the left common carotid artery and left middle cerebral artery of the COVID-19 patients.…”
Section: Role Of Atherosclerosis Imaging In Diabetes Patients During mentioning
confidence: 86%
“…This was the result of the inflammatory response and cytokine storm, which has also been considered as an important phenomenon for cardiac events in our review (Figure 2 ). Similarly, Alkhaibary et al [ 181 ] reported complete occlusion of the left common carotid artery and left middle cerebral artery of the COVID-19 patients.…”
Section: Role Of Atherosclerosis Imaging In Diabetes Patients During mentioning
confidence: 86%
“…( Table I ). Another 2 COVID-19 patients with CCA totally occluded have been published, 22 , 23 these cases were excluded from the review because they did not meet our inclusion criteria. All patients presented with stroke as the chief symptom, and COVID-19 manifestations of mild severity.…”
Section: Discussionmentioning
confidence: 99%
“…Roy et al ( 19 ) described a case who received surgical treatment 9 h after the stroke, unfortunately, the patient developed refractory hypoxemia in the postoperative period due to extensive pulmonary embolus and died. Alkhaibary et al ( 20 ) described a case presenting with a left common carotid artery complete occlusion and underwent surgery at least 72 h after worsening. All cases except the one presented by Alkhaibary et al ( 20 ) were treated according to the AHA/ASA 2018 Stroke Guidelines (48 h).…”
Section: Discussionmentioning
confidence: 99%
“…Alkhaibary et al ( 20 ) described a case presenting with a left common carotid artery complete occlusion and underwent surgery at least 72 h after worsening. All cases except the one presented by Alkhaibary et al ( 20 ) were treated according to the AHA/ASA 2018 Stroke Guidelines (48 h). In our case, although the patient was admitted to the hospital after 3 days of a low level of consciousness, we support the decision of the surgery as the patient was a 31-year-old previously healthy woman.…”
Section: Discussionmentioning
confidence: 99%